The role of decision support systems in enhancing the quality of financial statements of companies listed on the Damascus Stock Exchange"A field study" (Damascus University Journal for the economic and Political sciences, 2025)
The study aimed to determine the role of decision support systems represented by( availability of software, availability of databases, availability of human competencies) in enhancing the quality of financial statements. The descriptive and analytical approach was relied upon by applying it to companies listed on the Damascus Stock Exchange. A questionnaire was distributed to a sample of (100) individuals in the Finance Department and the Information Technology Department, and (87) valid questionnaires were retrieved for statistical analysis, representing (87)% of the total questionnaires distributed.The SPSS statistical program was relied upon to analyze the questionnaire, display descriptive statistics for the study variables based on arithmetic means and standard deviations, and test hypotheses using simple and multiple linear regression.The study found that there is a positive, significant relationship between decision support systems and enhancing the quality of financial statements, and the availability of software was the most influential variable in enhancing the quality of financial statements.
Keywords: decision support systems; software; databases; quality of financial statements